Assessment of Oral Hygiene Status and Attitude of Dental Students Towards Periodontal Care: An Introspective Mirror (Bangladesh Journal of Dental Research & Education, 2015)
Dental students represent the educated, urbanized, influential and motivated class of individuals. If motivated for oral health, they can transfer the same knowledge and behavior patterns to patients during their practices. With this intention, this study was planned. 200 dental students were assessed by a close-ended, four-item questionnaire. Oral hygiene was assessed by Simplified Oral Hygiene Index (OHI, Greene and Vermilion, 1964) and gingival condition by Gingival Index (GI, Loe & Silness, 1963). A positive change in attitude was observed from first to final year students. 100% of them used tooth brush and paste, but 88%, 88% 96%, 92% in first, second, third and fourth year cleaned their tongue; whereas 70%, 92%, 94%, 92% of them, respectively, were in favor of scientific method of brushing. 92%, 90%, 96%, 100%, respectively, felt visiting the dentist during gingival bleeding. Also, there was statistically significant improvement in GI between first and final year (p=0.00005), between second and final year (p=0.0003) students. OHI showed a consistent improvement from first to final year (p